The role of the general surgeon in diagnosis and treatment of neoplasms diseases in the surgical ward of the Podlaskie region - Snarska, Jadwiga; Puchalski, Zbigniew; Markiewicz, Włodziemierz; Wasielica, Mieczysław; Dadan, Jacek; Dudziak, Marek; Grajek, Zbysław; Krymski, Jerzy; Kuźmiuk, Janusz; Orłowski, Kazimierz; Róg, Marek; Sala, Norbert; et al. (Contemporary Oncology/Współczesna Onkologia, 2008)
An increase in morbidity of malignant neoplasms in older age has elevated mortality for these reasons especially in this group of people. The aim of the study was to evaluate the role of a general surgeon in treatment of malignant neoplasms in the Podlaskie region. The study was carried out based on questionnaires in 12 of 18 general surgery wards in our region. Questionnaire data concern the last five years, that is, years 2002–2006. The information obtained was compared to the data from the wards of oncological surgery. An increase in the number of patients operated on due to malignant neoplasms by both general and oncological surgeons was observed based on the results obtained in the study. The highest percentage of surgical procedures due to malignant neoplasms within the abdominal cavity are performed due to colorectal adenocarcinoma. Breast cancer, skin cancer and soft tissue cancer are mostly operated on in the Oncological Surgery Ward of the Białystok Centre of Oncology. Patients with pancreatic cancer, thyroid cancer, endocrine nodes cancer and primary and secondary cancer of the liver are operated on by general surgeons. Patients with advanced cancer complications, such as obstruction, haemorrhage and peritonitis, are sent on emergency to general surgery wards where they undergo operations. Moreover, patients are also referred to general surgery wards for invasive oncological diagnostics (laparoscopy) or with non-operational cancer for palliative operation or biopsy taking. The role of general surgeons is significant in treatment of malignant neoplasms. The results of the study prove that half of surgical procedures performed by general surgeons are oncological operations and their number can be compared in a year to the number of surgeries performed in the Centre of Oncology. Taking into consideration the facts mentioned above, oncological surgery should constitute half of a training period devoted to postgraduate education and residency of a general surgeon.